THE ANALYSIS OF FACTORS INFLUENCING DEUTSCHLANDTICKET REPURCHASE INTENTIONS: A STUDY USING THE THEORY OF PLANNED BEHAVIOR IN INTERNATIONAL STUDENTS AT JADE HOCHSCHULE WILHELMSHAVEN - Septiana, Vidya Ayu Dwi; Tjahjawati, Sri Surjani; Pramono, Tangguh Dwi; Fujiasti, Sherry Novalia (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
This study aims to analyze the factors influencing the repurchase intention of the Deutschlandticket among international students at Jade Hochschule Wilhelmshaven using the Theory of Planned Behavior (TPB) framework. The Deutschlandticket is a monthly public transportation subscription introduced by the German government as a long-term solution to the energy crisis and to promote environmentally friendly mobility. However, the ticket price increase from €49 to €58 per month in January 2025 presents new challenges in maintaining repurchase intention. This research examines the three core components of TPB attitude, subjective norms, and perceived behavioral control and their effects on the repurchase intention of the Deutschlandticket. The study employs a survey method with a sample of international students in Wilhelmshaven, analyzed using validity, reliability, and regression tests. Hypothesis testing reveals that all tested pathways are statistically significant. Structural model analysis shows that 67.1% of the variance in repurchase intention is explained by the three TPB constructs, indicating a strong model fit. However, the influence of environmental concern on subjective norms and perceived behavioral control individually remains modest. The results suggest that students' environmental concerns strengthen their attitudes, perceived control, and social pressures, ultimately leading to a higher intention to repurchase the Deutschlandticket despite the price increase. These findings offer important insights for policymakers and transport providers aiming to sustain ticket adoption rates through strategies emphasizing environmental benefits. It contributes to the understanding of sustainable consumer behavior and highlights the role of environmental concerns in shaping repurchase intentions within the public transportation sector.